Trapping and metabolism of radioiodinated PHIPA 3-10 in the rat myocardium - Eisenhut, Michael; Lehmann, Wolf-Dieter; Hull, William Edmund; Just, Wilhelm W.; Hoffend, Johannes; Zehelein, Jörg; Zimmermann, Rainer (Journal of nuclear medicine, 1997)
PHIPA 3-10 [13-(49-iodophenyl)-3-(p-phenylene)tridecanoic acid] is a p-phenylene-bridged, radioiodinated ω-phenyl fatty acid that has recently been developed to study coronary artery disease or cardiomyopathies. Here, we demonstrate that PHIPA 3-10 exhibits the characteristics of a long-chain fatty acid, including its ability to be efficiently taken up by myocytes and to function as a substrate for beta-oxidation before it is trapped. Methods: Myocardial metabolism of carrier-added and carrier-free 131I-PHIPA 3-10 preparations were investigated in rats in vivo and in isolated Langendorff rat hearts. Heart extracts were analyzed by high-performance liquid chromatography, negative-ion electrospray mass spectrometry and investigation of intracellular distribution using density-gradient centrifugation. Results: A single, rapidly formed metabolite was found in the heart extract and also, surprisingly, in the hydrolyzed lipids. The total amount of metabolite increased from 43% to 51% between 15 and 60 min postinjection. By high-performance liquid chromatography comparison with synthetic potential catabolites, the metabolite was assigned the namFXA 1-10 [11-(49-iodophe-nyl)-1-(p-phenylene)undecanoic acid] and was the product of one beta-oxidation cycle. Additional proof was obtained from the mass spectrometric analysis of the metabolite formed in vivo. The formation of this metabolite could be suppressed by Etomoxir, a carnitine palmitoyl transferase I inhibitor, indicating beta-oxidation of 131I-PHIPA 3-10 in mitochondria. Final evidence for the involvement of mitochondria in the degradation of 131I-PHIPA 3-10 was obtained by density-gradient centrifugation of homogenized rat heart tissue. The position of the labeled free PHIPA 3-10 and free metabolite peaked within the fraction containing mainly mitochondria. Conclusion: In spite of its bulky structure, 131I-PHIPA 3-10 is extracted by the myocardium in a manner similar to the extraction of the unmodified fatty acid analog, IPPA. The retention of PHIPA 3-10 in heart muscle results from the presence of the p-phenylene group, which prevents more than one beta-oxidation cycle. Intracellular free PHIPA 3-10 and free PHIPA 1-10 are present in the mitochondria, whereas most of the esterified metabolite was found in the cytosolic lipid pool. Hence, the rapid appearance of PHIPA 1-10 in the lipid pool must be accounted for by mitochondrial leakage or by an unknown in-out transport system.
Gesehen am 09.12.2024